Identification of local elastic parameters in heterogeneous materials using a parallelized femu method - Petureau, Louis; Doumalin, P.; Bremand, Fabrice (Zielona Góra: Uniwersytet Zielonogórski)
In this work, we explore the possibilities of the widespread Finite Element Model Updating method (FEMU) in order to identify the local elastic mechanical properties in heterogeneous materials. The objective function is defined as a quadratic error of the discrepancy between measured fields and simulated ones.
Keywords: identification; elasticity; heterogeneous material; genetic algorithms; parallel computations